Kampala's plausible urban flooding futures: Building insights through integrated collaborative modeling :Powerpoint - Sliuzas, R.V. (University of Twente, 2020)
This lecture presents: Floods in Kampala: all citizens are stakeholders; Kampala Capital City Authority and detailed study area; Kampala Rainfall data: filling the gaps; Soil property determination and mapping; Set of scenarios developed and discussed with stakeholders; Spatial visualization and indicators; Stakeholder engagement critical.